Do Current Water Subsidies Reach the Poor? - World Bank (Washington, DC, 2014)
There has been no hard empirical evidence to confirm or reject the hypothesis that water subsidies may be failing to reach the poor. This paper summarizes the results of some new survey-based research that estimates that estimates the value of the water subsidy received by individual households in two South Asian cities, and also estimates the income levels of these households. Using both pieces of information together, it is possible to evaluate the extent to which subsidies are actually reaching the poor. The analysis shows that about three quarters of the subsidies available to water utilities in the cities of Bangalore and Katmandu are delivered in a way which completely fails to reach the poor.